The Effect of Environmental Performance, Political Visibility, Environmental Cost on Corporate Social Responsibility Disclosure - Enung Nurhayati; Amir Hamzah; Intan Tansyah Garmanah (Future Science, 2022)
The aim of this research is to analyze and obtain empirical facts regarding Environmental Performance, Political Visibility, and Environmental Costs on Corporate Social Responsibility Disclosure. The population in this study consists of annual reports and financial statements of 18 manufacturing companies in the Textile and Garment Sub-Sector listed on the Indonesia Stock Exchange from 2014 to 2018. The sampling technique used is non-probability sampling in the form of quota sampling. Therefore, the sample in this study consists of 16 companies with a total of 80 observation data. The method used is descriptive and verificative with quantitative data. The analysis techniques used in this study are descriptive analysis, classical assumption tests, panel data regression analysis, coefficient of determination, and hypothesis testing using the Eviews ver.9.0 application program. The results show that Environmental Performance partially has a significant positive effect on Corporate Social Responsibility Disclosure. Political Visibility partially has a significant positive effect on Corporate Social Responsibility Disclosure. Environmental Costs partially have a significant positive effect on Corporate Social Responsibility Disclosure.